Using Instagram as a Media for Various Information about Yogyakarta (Content Analysis of the Instagram Account @wonderfuljogja) - Hadiati, Novianisa Asmar; Suksmawati, Herlina (Jurnal Dakwah dan Komunikasi, 2024)
This research aims to analyze the use of Instagram @wonderfuljogja as a medium that shares various information regarding public curiosity regarding trends in Yogyakarta. Instagram social media is a popular social platform and has many users, so it is very suitable as a forum for sharing information and sharing experiences in various fields. With a focus on analysis on the @wonderfuljogja account, it was carried out using a descriptive qualitative method using content analysis of the content presented, including the various types of content delivered, intensity of posts, use of images, and responses from @wonderfuljogja Instagram followers. The results of the content analysis of @wonderfuljogja Instagram content provide broader knowledge and insight regarding the use of Instagram in providing and conveying various information about Yogyakarta such as tourist destinations, Yogyakarta regional culture, events held in Yogyakarta and even various other general information. provide a social impact on the audience on Instagram. In conclusion, the Instagram account @wonderfuljogja is a platform that provides benefits as a medium that provides various information about Yogyakarta and can fulfill the public's information needs about Yogyakarta.